Uncertainty, Real Options, and Cost Behavior: Evidence from Washington State Hospitals - KALLAPUR, SANJAY; ELDENBURG, LESLIE (Journal of Accounting Research, 2005)
ABSTRACT This study tests an implication of the real‐options theory of investment, that uncertainty leads firms to prefer technologies with low fixed and high variable costs. In 1983, a change in Medicare reimbursement increased the uncertainty of revenues for hospitals. Using a sample of 831 departments in 59 Washington State hospitals over the 1977–1994 period, we find that the ratio of variable to total costs increased after 1983. This increase is not attributable to a gradual increase in the ratio over time: We estimate a significant increase after 1983 even after controlling for a time trend. Further, we find a greater increase in the variable‐to‐total cost ratio for hospitals that had higher percentages of Medicare patients, increasing our confidence in the conclusion that the change in cost behavior is attributable to Medicare's change in reimbursement.